Strategi Koordinasi Sumber Daya Manusia dalam Penyelenggaraan Event Budaya Berbasis Masyarakat (Studi Kasus Grebeg Sudiro) - Dina Kumalasari; Banindra Alan Patria; Bagas Nur Majid; Arnes Anandita (MAMEN: Jurnal Manajemen, 2026)
This study aims to analyze human resource coordination strategies in the implementation of Grebeg Sudiro, a community-based cultural festival in Sudiroprajan, Surakarta. The increasing scale of the festival and the involvement of large numbers of local residents create challenges in organizing human resources effectively and systematically. This research used a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation involving committee members, field coordinators, community leaders, and local residents participating in the event. The results show that human resource coordination in Grebeg Sudiro is carried out through structured task division, small-group coordination systems, direct supervision, and the utilization of digital communication media such as WhatsApp. The success of the coordination process is supported by community participation, mutual cooperation, and participatory leadership among organizers. However, several obstacles were identified, including differences in commitment levels, limited organizational experience, and occasional miscommunication during event implementation. The study concludes that the integration of community values with modern event management principles plays an important role in creating an organized and successful cultural festival. This research contributes to the development of community-based event management studies and provides practical references for organizing cultural festivals in Indonesia.